Mitigating hernia risk after abdominal surgery: a review article - Krishnan, Harini (International Surgery Journal, 2026)
Incisional hernias are a frequent and costly complication following abdominal surgery, with a reported incidence ranging from 10% to 50%, depending on patient factors, surgical approach, and follow-up method. This narrative review consolidates contemporary evidence on prevention strategies, with a focus on operative techniques, prophylactic mesh augmentation, and perioperative optimisation. High-quality randomized trials and meta-analyses support the small-bite closure technique (5 mm bites with 5 mm spacing), continuous slowly absorbable monofilament sutures, and maintaining a suture-to-wound length ratio of at least 4:1. Prophylactic mesh placement in selected high-risk populations (retrorectus or pre-peritoneal planes) substantially reduces the incidence of incisional hernias. Modifiable risk factors, such as obesity, smoking, diabetes, malnutrition, and surgical site infection, should be optimized before elective surgery. Emerging resorbable synthetic meshes may provide temporary reinforcement and reduce long-term foreign-body complications. However, data on their long-term durability remain limited. Herein, we present an evidence-based algorithm and four summary tables to assist clinicians in risk stratification and tailored prevention. Implementation requires surgeon training, institutional pathways, and systems for long-term outcome monitoring to confirm durable benefits.